A spatial econometric model for household electricity consumption in the Philippines - Sario, Marie Therese S.
Abstract (While electricity is regarded as a catalyst for economic development, twelve million Filipinos still do not have access to electricity. Most of the studies relating to energy focused on socio-demographic and economic context. This study seeks to propose a new perspective in household's electricity consumption by incorporating spatial dimension. To determine this three spatial econometric models were considered: Spatial Error Model, Spatial Lag Model, and Spatially Lagged X Model. The results of several model specification tests led to the conclusion that spatial lag model (SLM) with a spatial distance weight of 150km, is the most appropriate model for the study. The study show that by decomposing the results of the spatial lag model, a direct effect of Human Development Index, concrete national road, urban population, high electricity cost and low voltage on household's electricity consumption was observed.